(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Twin pregnancies is generally accepted as a high-risk condition with greater maternal and neonatal morbidity compared to singleton gestations. Objective: This study was designed to evaluate Obstetrics and Gynaecology difficulties and management strategies of different hospitals in Iraq, by recruiting and studying perinatal outcomes for twin pregnancies versus singleton pregnancies. Methods: A cross-sectional study was conducted among 70 patients who delivered from January 2024 to January 2025. The cohort was divided into twin pregnancies (n=37) and age-matched singleton pregnancies (n=33). Maternal characteristics, delivery data, and neonatal outcomes were recruited and assessed through medical records. Results: The mean age of women with twin pregnancies was higher (32.1 vs. 29.3 years), and Assisted Reproductive Technology was more prevalent (29.7% vs. 6.1%). Preeclampsia (18.9% vs. 3.0%) and preterm birth <37 weeks (67.6% vs. 12.1%) were significantly more common in women with twin pregnancies. The rate of cesarean section was significantly higher in the twin group (78.4% vs. 39.4%). Twin neonates included lower mean birth weight (2180g versus 3150g) and higher rates of low birth weight (64.9% versus 15.2%) and NICU admission (43.2% versus 15.2%). Conclusion: Twin pregnancies are noted to have far higher risks of obstetric complications, preterm delivery, and neonatal adverse outcomes compared to singleton pregnancies, where these findings identify the need for coordinated prenatal care and delivery planning in a tertiary care center to minimize risk and maximize perinatal outcome for both mother and infant.